Autism in women - under-diagnosed, under-served and under-represented - Morgan-Trimmer, Rachel (Murmurations: Journal of Transformative Systemic Practice, 2022)
Autism has historically been seen as primarily a male issue, and these attitudes still persist. The result is that autistic women and girls are going undiagnosed. This leads to huge problems with mental illness, inability to access the services and support they need, and significant social and professional issues, such as long-term unemployment. This article looks at some of the specific issues that affect autistic women, and how to address these, so that autistic women and girls can live the fulfilling lives they deserve.